A family affair? Post-imperial Estonian Orthodoxy and its relationship with the Russian Mother Church, 1917–23. Issue 3 (1st October 2020) - Paert, Irina
ABSTRACT: As the First World War shattered the old empires, Orthodox Christians in former imperial territories faced a dilemma. Should they remain loyal to their Russian "Mother Church, " from which they were separated by physical and ideological borders, or should they pursue autonomy and break away from their former canonical centre? This article deals with the evolution of the Estonian part of Riga diocese into an autonomous Orthodox Church, focusing on the negotiations, compromises, pluralism, and realpolitik that characterized this process. The reconfiguration of Riga diocese in 1917–23 and the emergence of the autonomous Estonian Orthodox Church under the patriarch of Constantinople occurred under the influence of three factors: first, the political formation of Estonian statehood; second, the violence of the Bolshevik takeover and the Civil War; and, third, the temporary decentralization of the Russian Church. Pointing out that Patriarch Tikhon was willing to negotiate various forms of church autonomy in the Baltic and there was support for remaining under the jurisdiction of Moscow, the article argues that the change of jurisdiction was in itself a sign of the Estonian Church's agency when it came to fulfilling its desire for ecclesiastical autonomy.